Washability of e-textiles: current testing practices and the need for standardization - Rotzler, Sigrid; Krshiwoblozki, Malte von; Schneider-Ramelow, Martin (Textile research journal, 2021)
Washability is seen as one of the main obstacles that stands in the way of a wider market success of e-textile products. So far, there are no standardized methods for wash testing of e-textiles and no protocols to comparably assess the washability of tested products. Thus, different e-textiles that are deemed equally washable by their developers might present with very different ranges of reliability after repeated washing. This paper presents research into current test practices in the absence of e-textile-specific standards. Different testing methods are compared and evaluated and the need for standardized testing, giving e-textile developers the tools to comparably communicate and evaluate their products’ washability, is emphasized.